The jumping spider Tapsatella albocastanea, a new genus and species from Argentina (Araneae: Salticidae: Freyina) - Rubio, Gonzalo Daniel; Stolar, Cristian Eric; Nadal, María F.; Baigorria, Julián E. (Peckham Society, 2020)
Tapsatella albocastanea, new genus and species (Araneae, Salticidae) is described from specimens recently collected in a quebrachal forest in Chaco Province, Argentina. The dorsal stripes, shape of the tegulum, presence of small spherical spermathecae and shape of the external epigynum suggest that this species is a relative of some Wedoquella and Phiale. It differs from both of these genera by the presence of a peculiar border between tegulum divisions, a different structure and arrangement of copulatory ducts, and an elongate, depressed, and much narrower carapace.